Penerapan Metode Bernyanyi untuk Meningkatkan Pengetahuan Sikat Gigi pada Peserta Didik Usia 5-6 Tahun Di TK Aisyiyah Bustanul Athfal II Perumnas Cabang Karunrung Kota Makassar - Damayanti, Eka; Sri Wahyuni, Khafifa; Rahman, Ulfiani; Rismawati MS; Hamsah (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2022)
Knowledge about brushing teeth is important for early childhood to be able to maintain dental and oral hygiene from an early age. Knowledge about brushing teeth starting from the importance of brushing teeth to how to brush teeth needs to be taught from the beginning which will be useful for children’s oral and dental health. Therefore, it is important to do the right stimulation, one of which is using the singing method so that children aged 5-6 years can quickly realize the importance of brushing their teeth and know how to brush their teeth properly and correctly. This community service research in the form of service learning was conducted at Aisyiyah Kindergarten Bustanul Athfal ll Perumnas Karunrung Branch with a total of 3 participants. The instrument used was a checklist sheet and an evaluation sheet for the implementation of the intervention. Data were analyzed using descriptive statistics. The results of the service research show that students have knowledge of brushing their teeth through the singing method. The findings in this devotional research imply that teachers can use various fun methods such as singing in teaching children about brushing their teeth so that children can also apply it in a fun way without being forced.